2012
DOI: 10.1021/ja304009b
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Millisecond Time Scale Near-Infrared Emission in Polynuclear Chrome(III)–Lanthanide(III) Complexes

Abstract: This work illustrates a simple approach for optimizing long-lived near-infrared lanthanide-centered luminescence using trivalent chromium chromophores as sensitizers. Reactions of the segmental ligand L2 with stoichiometric amounts of M(CF(3)SO(3))(2) (M = Cr, Zn) and Ln(CF(3)SO(3))(3) (Ln = Nd, Er, Yb) under aerobic conditions quantitatively yield the D(3)-symmetrical trinuclear [MLnM(L2)(3)](CF(3)SO(3))(n) complexes (M = Zn, n = 7; M = Cr, n = 9), in which the central lanthanide activator is sandwiched betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 62 publications
1
68
0
3
Order By: Relevance
“…16,17 Piguet and co-workers reported the enhancement of the luminescence of polynuclear complexes by effective energy transfer from Cr(III) to lanthanide(III) ions. 18 We also recently demonstrated temperature-sensitive luminophores composed of Eu-(III) and Tb(III) complexes. 19 Specific metal-to-metal interactions in polynuclear lanthanide complexes induce active magnetic and photophysical behavior.…”
mentioning
confidence: 98%
“…16,17 Piguet and co-workers reported the enhancement of the luminescence of polynuclear complexes by effective energy transfer from Cr(III) to lanthanide(III) ions. 18 We also recently demonstrated temperature-sensitive luminophores composed of Eu-(III) and Tb(III) complexes. 19 Specific metal-to-metal interactions in polynuclear lanthanide complexes induce active magnetic and photophysical behavior.…”
mentioning
confidence: 98%
“…It is reported that La 3 Ga 5 GeO 14 :Cr 3+ exhibited excellent near infrared emission at around 980 nm with broadband absorption at 370~520 nm and 560~800 nm [32,33]. It can be deduced that Cr 3+ could efficiently transfer its absorbed energy to Yb 3+ in La 3 Ga 5 GeO 14 through resonant energy transfer based on the matching of emission energy level of Cr 3+ and absorption energy level of Yb 3+ at around 980 nm, which are proved by many previous work [10,21,22,24]. The absence of absorption at 520~560 nm makes Cr 3+ probable to sensitize Yb 3+ -Er 3+ with room-temperature UC luminescence of Er 3+ in this wavelength range, which is further convinced by the fact that La 3+ site could accommodate Yb 3+ /Er 3+ and Ga 3+ site could accommodate Cr 3+ with less distortion defects as emission killer.…”
Section: Introductionmentioning
confidence: 63%
“…Herein, to get high energy transfer efficiency, short distance and the matching of energy levels between sensitizer(dye molecules) and acceptor(Yb 3+ -Er 3+ ) are required for resonant energy transfer pathway [19,20]. It is known that transition metal(TM) ions have the broadband absorption feature, which is commonly utilized to sensitize Stokes luminescence of lanthanide ions [21,22]. Analogously, they could also be used as a broadband sensitizer for UC luminescence [7,10], for instance, the Cr 5+ -Er 3+ [23], V 3+ -Er 3+ [24,25] and V 3+ -Pr 3+ [26] systems.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality in octahedral systems is interesting because many metal cations favor octahedral geometry and can provide more complex, dynamic, and functional systems including triple helicates [55,56], circular helicates [57,58], tetrahedral clusters [59], and heteronuclear helicates consisting of lanthanide and transition metal cations [60][61][62]. Chirality induction in octahedral metal complexes has been widely investigated using chiral ligands, starting with Werner's pioneering works [29,30], in which most metal centers were kinetically inert; their complexations often required long periods of time for completion, and purification procedures were required for obtaining diastereo-and enantiopure complexes.…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 99%